From Caliphate To Civil State: The Relevance Of Hasan Al-Banna And Ali Abd Al-Raziq's Thought To Contemporary Islamic Politics: English - Moh. Sholeh Baharis; Wiwik Setiyani (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2025)
This article discusses the ideological contest between Islamism and Secularism in the thinking of two important figures of the 20th century: Hasan al-Banna and Ali Abd al-Raziq. The main issues in this study are: first, how the political thought of Hasan al-Banna and Ali Abd al-Raziq shaped the vision of an Islamic state or a civil state; and second, to what extent the concepts of Hakimiyah and secularism are contradictory or, in fact, open up opportunities for compromise and dialogue in the context of modernity. This study uses a library research approach with a critical-comparative analysis method of the texts and ideas of the two figures. The results of the analysis show that al-Banna (and Qutb) emphasize the integration of religion and politics based on Sharia, while Abd al-Raziq proposes the desacralization of power and opens space for modern political ijtihad. However, this study does not stop at the dichotomous opposition between Islamism and secularism, but rather attempts to explore opportunities for conceptual dialogue between the two in constructing an ethical, rational, and contextual Islamic political paradigm. The findings of this study confirm that the debate between the two ideologies reflects an epistemological conflict between the theology of power and the universal ethics of Islam, while also offering space for synthesis in the effort to formulate a new relationship between religion, the state, and modernity. Thus, the discourse of Islamism and secularism is no longer understood as a binary opposition, but as a creative dialectic that enriches the dynamics of contemporary Islamic politics.